Nature urbaine et urbanité dans la station touristique de Salou (Espagne), au travers de l’étude : d’un parc-promenade, d’un paseo, d’un parc urbain - Jean Rieucau (EchoGéo)
The forested public areas become a stake of the touristic appeal of coastal destinations on the Mediterranean coast of Spain. The municipalities steer the urban recovery policies on the beaches, beach heights, along the coastal line, at the expense of anarchical urbanization, inherited from the years 1960 (hotels, camping ground). The landscapers, confronted with the split between touristic city and “resident” city, use exotic vegetation, out of context (palm tree) for public areas developed into tourism, and resort to indigenous nature (olive trees, cypress) for common areas for the permanent residents.